Origins of sequence diversity in the malaria vaccine candidate merozoite surface protein-2 (MSP-2) in Amazonian isolates of Plasmodium falciparum - Hoffmann, Erika H. E.; Malafronte, Rosely S.; Moraes-Avila, Sandra L.; Osakabe, Ana Lucia; Wunderlich, Gerhard; Durham, Alan M.; Ribolla, Paulo Eduardo M.; del Portillo, Hernando A.; Ferreira, Marcelo U. (Elsevier B.V., 2006)
The recent evolution of Plasmodium falciparum is at odds with the extensive polymorphism found in most genes coding for antigens. Here, we examined the patterns and putative mechanisms of sequence diversification in the merozoite surface protein-2 (MSP-2), a major malarial repetitive surface antigen. We compared the msp-2 gene sequences from closely related clones derived from sympatric parasite isolates from Brazilian Amazonia and used microsatellite typing to examine, in these same clones, the haplotype background of chromosome 2, where msp-2 is located. We found examples of msp-2 sequence rearrangements putatively created by nonreciprocal recombinational events, such as replication slippage and gene conversion, while maintaining the chromosome haplotype. We conclude that these nonreciprocal recombination events may represent a major source of antigenic diversity in MSP-2 in P falciparum populations with low rates of classical meiotic recombination. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: malaria; MSP-2; recombination; antigenic diversity; replication slippage; gene conversion